Radiologic imaging and its current importance in breast cancer management - Dagar, Nisha; Sarin, Monu; Yadav, Piyush; Thidwar, Rajdeep (Frontiers in Radiology, 2026)
IntroductionThis study examines the approaches used for cancer screening in women, insisting on the roles of mammography, breast ultrasound, breast MRI, computed tomography (CT), and positron emission tomography. Mammography is still the key method for early detection, with modern digital technology boosting image quality and diagnostic accuracy. Breast MRI provides increased sensitivity for high-risk individuals, and it is recommended to be used with mammography for full screening.MethodsThis review article provides a comprehensive assessment of breast imaging techniques, focussing on screening recommendations and advancements in mammography, ultrasonography, MRI, CT, and PET. These methods provide a multidisciplinary approach to improving breast cancer detection, diagnosis, and personalized care. Early detection is necessary for less aggressive treatment. Digital breast tomosynthesis consists of contrast-enhanced spectral mammography, molecular breast imaging, MRI, and USG.ResultsMammography remains the primary imaging modality for detecting breast abnormalities, including cancer. The use of standardized interpretation systems improves the communication of findings. The present paper summarizes the primary disputes surrounding breast cancer management.ConclusionAccording to the literature, low-dose mammography is the only radiographic technique that has significantly impacted the diagnosis, staging, and patient follow-up for asymptomatic breast cancer screening. Mammography is also the only accurate screening test for breast imaging. Implications for practice.